Preparation method of geopolymer concrete with mixture of thermally activated muck and cement and prefabricated floor slab

Through the preparation method of thermally activated slag and calcium hydroxide mixture, the problems of high energy consumption and environmental pollution in traditional concrete manufacturing are solved, and the reuse of slag and resource recycling are realized, which significantly reduces production costs and environmental impacts. .

CN119430763APending Publication Date: 2025-02-14SHEN ZHEN SHI JIN ZHONG JI TUAN GU FEN YOU XIAN GONG SI +4
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411613785.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

During the traditional concrete manufacturing process, relying on a large amount of natural resources leads to high energy consumption and environmental pollution, and at the same time, the accumulation of building waste is serious.

Method used

By preparing a polyconcrete mixture of thermally activated slag and calcium hydroxide, building slag is used as raw material to dry, screen, mix active excitation and alkaline exciter to prepare excellent mechanical properties and durability Ground polymer concrete.

Benefits of technology

Reliance on traditional concrete raw materials has been achieved, energy consumption and environmental pollution have been reduced, resource recycling has been promoted, production costs have been significantly reduced, and the overall performance of concrete has been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119430763A_ABST
    Figure CN119430763A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of geopolymer concrete prepared from thermally activated muck and a cement mixture. The preparation method comprises the following steps: a, preparing raw materials; b, raw material pretreatment; c, activating; d, preparing neat paste; and e, preparing concrete. The invention further provides a pre-floor slab, and the main body material of the pre-floor slab is the geopolymer concrete prepared from the thermally activated muck and the cement mixture prepared by the preparation method. According to the method, the muck obtained in project earthwork excavation is used as a main raw material, waste recycling is achieved, pollution of muck waste accumulation and landfill to the environment is reduced, dependence on natural resources is reduced, and therefore the environmental protection property and sustainability of the whole preparation process are improved, the muck is used as the main raw material, and the cost is reduced. And an efficient preparation process is combined, so that the production cost of the concrete is remarkably reduced. In addition, specific additives and reinforcing agents are added, so that the cost performance and market competitiveness of the concrete are further improved.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field] The invention relates to the technical field of building materials, and in particular to a method for preparing geopolymer concrete of a mixture of heat-activated slag and cement, and a prefabricated floor slab of slag geopolymer concrete prepared by the preparation method. [Background technology] The traditional concrete manufacturing process not only relies on a large amount of natural resources, such as sand and stone aggregates, but also its energy consumption and environmental pollution problems in the production process have been criticized. Especially in the cement production process, data show that for every ton of Portland cement produced, about 1.5 tons of limestone and a large amount of coal and electricity are required, and a large amount of carbon dioxide is also emitted. Studies have shown that greenhouse gas emissions generated by cement production account for a considerable proportion of total human emissions, exacerbating the global greenhouse effect. In addition, the raw materials of traditional concrete mainly come from natural resources, such as sand and stone aggregates. The mining of these resources not only consumes a lot of energy, but also may lead to resource depletion and ecological damage. With the increase in the use of concrete, the demand for raw materials such as sand and stone has also continued to rise. Some areas have already experienced problems of sand and stone resource shortages and ecological damage.

[0003] In addition, with the acceleration of urbanization, the amount of waste generated by construction projects is increasing, which has brought a heavy burden to the environment. [Summary of the invention] The purpose of the present invention is to provide a method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide, which can utilize waste such as construction slag as raw materials, reduce dependence on traditional raw materials, reduce energy consumption and emissions in the production process, and reduce environmental pollution, aiming to solve the above-mentioned problems existing in traditional concrete manufacturing.

[0005] The present invention is achieved by the following technical solutions: The method for preparing geopolymer concrete of a mixture of heat-activated slag and cement comprises the following steps: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and sieving the slag in step a to obtain dry slag powder and slag particles of suitable particle size; c. Activation: adding the slag powder and the slag particles in step b to mix with ordinary cement, and calcining them under high temperature conditions to obtain an activated mixture; d. Preparation of pure slurry: mixing the activated mixture in step c with an alkaline activator to prepare a pure slurry material; e. Concrete preparation: the clean slurry material in step d is mixed with coarse aggregate, fine aggregate and admixture to obtain heat-activated slag and cement mixture geopolymer concrete slurry, and a reinforcing agent is added to the heat-activated slag and cement mixture geopolymer concrete slurry.

[0006] In traditional concrete production, the manufacturing process of cement not only requires a lot of energy, but also releases a lot of carbon dioxide, which has an adverse impact on the environment. The present invention directly obtains slag as raw material from the project earthwork excavation, realizes the reuse of construction waste, not only reduces the exploitation of natural resources, but also effectively solves the environmental problems caused by slag accumulation, and promotes the recycling of resources. Specifically, by drying and screening the slag for pretreatment, and calcining under high temperature conditions, the activity of the slag can be fully stimulated, and the dependence on high-energy consumption materials such as cement in the subsequent concrete preparation process can be reduced, thereby reducing carbon emissions, which meets the current requirements of green buildings and sustainable development. By adding an alkaline activator to the activated mixture for geopolymerization reaction, a geopolymer with a mesh structure is generated. The generated geopolymer has excellent mechanical properties and durability, so that the prepared concrete performs better in terms of compression resistance, impermeability, and frost resistance. At the same time, the addition of a reinforcing agent further improves the overall performance of the concrete, making it suitable for more complex engineering environments. The present invention uses cheap slag as a raw material, and prepares high-performance geopolymer concrete through simple process steps, which significantly reduces the production cost. In addition, since geopolymer concrete has a long service life and low maintenance costs, this method also has significant economic benefits in the long run.

[0007] Preferably, in the present invention, the drying temperature in step b is 100-110° C., the drying time is 24 hours, and the particle size of the slag particles is less than or equal to 1.5 mm and 5-25 mm.

[0008] The drying process mainly removes the moisture in the slag in gaseous form through heat conduction and convection. The drying temperature is set at 100~110°C because at this temperature, the activity of water molecules is enhanced, and it is easy to migrate from the inside of the slag to the surface and be discharged. At the same time, the 24-hour drying time ensures that the moisture has sufficient time to escape from the slag, achieving the ideal drying effect.

[0009] In concrete preparation, the particle size distribution of aggregates has an important influence on the physical and mechanical properties of concrete. By screening the soil particles into different particle size ranges, the aggregate gradation of concrete can be optimized. The filling effect of small-size particles can reduce the porosity inside the concrete and increase the density; while large-size particles can form a stable skeleton structure to resist external pressure. This particle size combination helps to achieve high strength and good working performance of concrete.

[0010] Preferably, in the present invention, the high temperature condition in step c is 700-750° C., the calcination time is 2 hours, and the particle size of the slag particles is less than or equal to 1.5 mm.

[0011] High-temperature calcination can effectively stimulate the activity of slag, causing the aluminosilicate minerals therein to undergo phase change and activation, thereby improving the reactivity with materials such as cement. This helps to form a more stable and better-performing geopolymer gel in subsequent steps. The use of slag particles with a particle size less than or equal to 1.5 mm screened out in step c helps to improve the calcination effect and the performance of subsequent concrete. This is because the slag particles with small particle sizes have a larger specific surface area and can more fully contact and react with the alkali activator, thereby increasing the amount and quality of the geopolymer gel. In addition, high-temperature calcination can be carried out in a muffle furnace to ensure the uniformity and stability of the calcination process. The muffle furnace has good temperature control and regulation capabilities, and can provide a constant calcination environment, thereby ensuring the uniform activation of slag particles and the generation of high-quality geopolymer gel.

[0012] Preferably, in the present invention, the alkaline activator in step d is sodium hydroxide and water glass, and the added amount thereof is controlled between 6% and 10% by weight of the total amount of the liquid activator and the solid raw materials.

[0013] Sodium hydroxide and water glass, as alkaline activators, play a vital role in geopolymerization. Sodium hydroxide can destroy the aluminosilicate structure in the slag and dissolve it in the alkaline solution; while water glass provides abundant silicate ions, which react with the dissolved aluminum ions to form a geopolymer gel with a network structure. This gel can fill the pores inside the concrete, improve the density and strength of the concrete, and give the concrete excellent durability and impermeability.

[0014] The amount of alkaline activator added has a significant effect on the performance of concrete. An appropriate amount of activator can fully activate the activity of the slag and promote the occurrence of geopolymerization, thereby improving the performance of the concrete. However, when the amount added is too high, the excess activator may form free alkali metal ions in the concrete, which may react with other components in the concrete, resulting in a decrease in the performance of the concrete. Therefore, accurately controlling the amount of activator added between 6% and 10% can more effectively activate the activity of the slag and promote the occurrence of geopolymerization, thereby preparing a heat-activated slag and cement mixture geopolymer concrete with excellent performance.

[0015] Preferably, in the present invention, the water-to-solid ratio in the mixing process of step e is 20% to 30%.

[0016] Water is a necessary condition for hydration reaction. The right amount of water can promote the hydration reaction between the active ingredients in the geopolymer material and the alkaline activator to form a stable gel structure. However, too much water will increase the porosity inside the concrete and reduce the strength; too little water will affect the hydration reaction and is also not conducive to the development of strength. Therefore, controlling the water-solid ratio within the range of 20%~30% can ensure the smooth progress of the hydration reaction and obtain good strength performance.

[0017] Preferably, in the present invention, the weight mix ratio of the slag polymer concrete in step e is activated mixture: water glass: sodium hydroxide: fine aggregate: coarse aggregate: water = 1: 0.3~0.4: 0.3~0.4: 2~3: 2~3: 0.1~0.2, the coarse aggregate is the slag particles with a particle size of 5~25 mm, and the fine aggregate is medium sand with a particle size of 1.0mm~2.0mm and a fineness modulus of 2.3~3.0.

[0018] The performance of concrete depends on the properties of its components and the interaction between them. The mix design achieves the best synergy between the components of concrete by precisely controlling the proportions of the components. The activated mixture, as a cementitious material, works together with water glass and sodium hydroxide to form a geopolymer structure, providing a strength basis for concrete. Fine aggregate and coarse aggregate enhance the mechanical properties and durability of concrete through filling and skeleton effects. Specifically, coarse aggregate and fine aggregate play a filling and skeleton role in concrete. Coarse aggregate (soil particles with a particle size of 5-25 mm) can form a stable skeleton structure and improve the compressive strength and crack resistance of concrete; while fine aggregate (medium sand with a particle size of 1.0 mm-2.0 mm and a fineness modulus of 2.3-3.0) can fill the gaps between coarse aggregates and improve the density and durability of concrete. This coarse and fine combination helps to optimize the performance of concrete.

[0019] Preferably, in the present invention, the admixture includes S105 grade ground granulated blast furnace slag and F class fly ash, the particle size of the F class fly ash is less than 45μm, the specific surface area is 400m² / kg~450m² / kg, and the dosage range is 5~8%; the particle size of the S105 grade ground granulated blast furnace slag is less than 45μm, the specific surface area is 500m² / kg~520m² / kg, and the dosage range is 4~6%.

[0020] As active mineral admixtures, fly ash and slag mainly play a filling effect, a pozzolanic effect and a micro-aggregate effect in geopolymer concrete of heat-activated slag and cement mixture. First, the particle size of fly ash and slag is small, which can fill the gaps between cement particles, reduce the porosity of concrete, and improve the density of concrete. Secondly, the active components in fly ash and slag can undergo secondary hydration reaction with cement hydration products (such as calcium hydroxide) to generate more hydration products (such as hydrated calcium silicate gel), which can fill the pores inside the concrete and further improve the density and strength of the concrete. Finally, the fine particles in fly ash and slag can be dispersed in concrete as micro-aggregates, play a supporting and dispersing role, and improve the mechanical properties and durability of concrete. In addition, the addition of fly ash and slag can also adjust the alkalinity of concrete, reduce the content of calcium hydroxide in concrete, and thus reduce the risk of alkali-aggregate reaction of concrete. At the same time, the addition of these admixtures can also improve the crack resistance of concrete, reduce shrinkage deformation, etc.

[0021] Preferably, in the present invention, the reinforcing agent is steel fiber, and the dosage range is 1.0% to 1.5%.

[0022] As a reinforcing agent, steel fiber can significantly improve the tensile strength and crack resistance of concrete. When concrete is subjected to tension, steel fiber can bear part of the tension, thereby delaying the formation and development of cracks. This helps to improve the overall strength and durability of concrete. Secondly, the addition of steel fiber can improve the toughness of concrete, so that it can better absorb energy and reduce damage when it is impacted or vibrated. This is of great significance for improving the performance of concrete in harsh environments. In addition, by controlling the dosage of steel fiber within the range of 1.0%~1.5%, it is possible to effectively control costs while ensuring the improvement of concrete performance.

[0023] The present invention also proposes a prefabricated floor slab, comprising a floor slab body, on which a plurality of truss bars are evenly arranged, and the material of the floor slab body is the heat-activated slag and cement mixture geopolymer concrete prepared by the above-mentioned heat-activated slag and cement mixture geopolymer concrete preparation method.

[0024] Compared with the prior art, the present invention has the following advantages: The present invention utilizes the slag obtained from the earthwork excavation of the project as the main raw material, which not only realizes the reuse of waste, reduces the pollution of the environment caused by the accumulation and landfill of slag waste, but also reduces the dependence on natural resources, thereby improving the environmental protection and sustainability of the entire preparation process. By drying, screening, activating and mixing the slag with an alkaline solution, the physical and chemical properties of the slag are effectively improved, and the slag is converted into a geopolymer concrete with excellent mechanical properties and durability. These steps work together to improve the overall performance of the final product. During the preparation process, the process parameters of each step, such as drying temperature, calcination temperature, calcination time, raw material particle size and the proportion of each component, are precisely controlled to achieve high efficiency of the process and stability of the product. Using slag as the main raw material and combining it with an efficient preparation process significantly reduces the production cost of concrete. At the same time, by adding specific admixtures and reinforcing agents, the cost performance and market competitiveness of concrete are further improved.

[0025] In summary, the present invention achieves significant advantages in environmental protection, performance optimization, flexible and efficient process, cost savings and wide application through an innovative method for preparing geopolymer concrete of a mixture of heat-activated slag and calcium hydroxide and its application in the field of construction.

Brief Description of the Drawings

[0027] Figure 1 Schematic diagram of the preparation process of Examples 1-3 of the present invention; Figure 2 This is a schematic diagram of the structure of Embodiment 4 of the present invention; Figure 3 This is a mise analysis diagram of precast floor slab concrete according to Example 4 of the present invention; Figure 4 This is a mise analysis diagram of the reinforcement of the prefabricated floor slab in Example 4 of the present invention. [Specific implementation method] In order to make the technical problems, technical solutions and beneficial effects solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0029] Example 1 This embodiment provides a heat-activated slag and cement mixture geopolymer concrete, in which the weight mix ratio is: activated mixture: water glass: sodium hydroxide: fine aggregate: coarse aggregate: water = 1:0.35: 0.3:2.6:2:0.1.

[0030] The activated mixture includes slag particles with a particle size less than or equal to 1.5 mm, slag powder and ordinary cement; the fine aggregate is medium sand with a particle size of 1.8 mm and a fineness modulus of 2.5; and the coarse aggregate is slag particles with a particle size of 2 to 25 mm.

[0031] The preparation method comprises the following steps: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and screening the slag in step a, the drying temperature is 100-110° C., and the drying time is 24 hours, so as to obtain dry slag powder and slag particles of suitable particle size, wherein the slag particles include two specifications of particle size less than or equal to 1.5 mm and 2-25 mm; c. Activation: adding the slag powder and slag particles with a particle size of less than or equal to 1.5 mm described in step b to ordinary cement, and calcining them in a muffle furnace at 700-750° C. for 2 hours to obtain an activated mixture; d. Preparation of pure slurry: mixing the activated mixture in step c with water glass and sodium hydroxide to prepare a pure slurry material; e. Concrete preparation: The slurry material described in step d is mixed with coarse aggregate (slag particles with a particle size of 2 to 25 mm), fine aggregate (medium sand with a particle size of 1.8 mm) and admixtures (5% of Class F fly ash and 5% of S105 grade ground granulated blast furnace slag) to obtain a heat-activated slag and cement mixture geopolymer concrete slurry, and 1.5% of steel fiber is added to the heat-activated slag and cement mixture geopolymer concrete slurry.

[0032] After the heat-activated slag and cement mixture geopolymer concrete slurry is prepared, the heat-activated slag and cement mixture geopolymer concrete slurry is poured into a mold (150mm×150mm×150mm cubic mold, a total of 12 molds are cast), and a vibration table and manual plugging are used to make it dense, and then it is smoothed and covered with plastic film for curing for 28 days.

[0033] Example 2 This embodiment provides a heat-activated slag and cement mixture geopolymer concrete, in which the weight mix ratio is: activated mixture: water glass: sodium hydroxide: fine aggregate: coarse aggregate: water = 1:0.4: 0.3:3:2.5:0.2.

[0034] The activated mixture includes slag particles with a particle size less than or equal to 1.5 mm, slag powder and ordinary cement; the fine aggregate is medium sand with a particle size of 1.8 mm and a fineness modulus of 2.5; and the coarse aggregate is slag particles with a particle size of 2 to 25 mm.

[0035] The preparation method comprises the following steps: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and screening the slag in step a, the drying temperature is 100-110° C., and the drying time is 24 hours, so as to obtain dry slag powder and slag particles of suitable particle size, wherein the slag particles include two specifications of particle size less than or equal to 1.5 mm and 2-25 mm; c. Activation: adding the slag powder and slag particles with a particle size of less than or equal to 1.5 mm described in step b to ordinary cement, and calcining them in a muffle furnace at 700-750° C. for 2 hours to obtain an activated mixture; d. Preparation of pure slurry: mixing the activated mixture in step c with water glass and sodium hydroxide to prepare a pure slurry material; e. Concrete preparation: The slurry material in step d is mixed with coarse aggregate (slag particles with a particle size of 2 to 25 mm), fine aggregate (medium sand with a particle size of 1.8 mm) and admixture (6% of Class F fly ash and 5% of S105 grade ground granulated blast furnace slag) to obtain a heat-activated slag and cement mixture geopolymer concrete slurry, and 1.2% of steel fiber is added to the heat-activated slag and cement mixture geopolymer concrete slurry.

[0036] After the heat-activated slag and cement mixture geopolymer concrete slurry is prepared, the heat-activated slag and cement mixture geopolymer concrete slurry is poured into a mold (150mm×150mm×150mm cubic mold, a total of 12 molds are cast), and a vibration table and manual plugging are used to make it dense, and then it is smoothed and covered with plastic film for curing for 28 days.

[0037] Example 3 This embodiment provides a heat-activated slag and cement mixture geopolymer concrete, in which the weight mix ratio is 1:0.4:0.4:2.5:2:0.15 for activated mixture:water glass:sodium hydroxide:fine aggregate:coarse aggregate:water.

[0038] The activated mixture includes slag particles with a particle size less than or equal to 1.5 mm, slag powder and ordinary cement; the fine aggregate is medium sand with a particle size of 1.8 mm and a fineness modulus of 2.5; and the coarse aggregate is slag particles with a particle size of 2 to 25 mm.

[0039] The preparation method comprises the following steps: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and screening the slag in step a, the drying temperature is 100-110° C., and the drying time is 24 hours, so as to obtain dry slag powder and slag particles of suitable particle size, wherein the slag particles include two specifications of particle size less than or equal to 1.5 mm and 2-25 mm; c. Activation: adding the slag powder and slag particles with a particle size of less than or equal to 1.5 mm described in step b to ordinary cement, and calcining them in a muffle furnace at 700-750° C. for 2 hours to obtain an activated mixture; d. Preparation of pure slurry: mixing the activated mixture in step c with water glass and sodium hydroxide to prepare a pure slurry material; e. Concrete preparation: the slurry material described in step d is mixed with coarse aggregate (slag particles with a particle size of 2 to 25 mm), fine aggregate (medium sand with a particle size of 1.8 mm) and admixture (4% of Class F fly ash and 6% of S105 grade ground granulated blast furnace slag) to obtain a heat-activated slag and cement mixture geopolymer concrete slurry, and 1% of steel fiber is added to the heat-activated slag and cement mixture geopolymer concrete slurry.

[0040] After the heat-activated slag and cement mixture geopolymer concrete slurry is prepared, the heat-activated slag and cement mixture geopolymer concrete slurry is poured into a mold (150mm×150mm×150mm cubic mold, a total of 12 molds are cast), and a vibration table and manual plugging are used to make it dense, and then it is smoothed and covered with plastic film for curing for 28 days.

[0041] Performance test: The heat-activated slag and cement mixture geopolymer concrete prepared in Examples 1-3 was tested for setting time of concrete slurry according to the Standard for Test Methods for Performance of Ordinary Concrete Mixtures (GB / T 50080-2016), and the 7d compressive strength and 28d compressive strength of concrete were tested according to the Standard for Test Methods for Mechanical Properties of Ordinary Concrete (GB / T50081-2019). The test results are shown in Table 1.

[0042] Table 1 Performance test results of geopolymer concrete made of thermally activated slag and cement mixture

[0043] As shown in Table 1, the 7d average compressive strength of Examples 1-3 can reach up to 25.3MPa, and the 28d average compressive strength can reach up to 35.6MPa, with excellent mechanical properties. The project waste slag as the main raw material of concrete can meet the national standards and can be used as a substitute for ordinary concrete in most engineering projects, which can significantly reduce the dependence on traditional concrete raw materials (such as sand and stone aggregates). It not only reduces the energy consumption in the process of raw material mining, but also reduces the emission of related greenhouse gases (such as carbon dioxide), thereby effectively alleviating the global greenhouse effect, realizing the reasonable secondary use of industrial waste resources (i.e. slag), promoting the recycling of resources, saving construction costs, and greatly reducing the transportation and processing costs of construction slag, bringing significant economic benefits to enterprises.

[0044] Embodiment 4. This embodiment provides a prefabricated floor slab, comprising a floor slab body 1, on which a plurality of truss bars 2 are evenly arranged. The material of the floor slab body 1 is the heat-activated slag and cement mixture geopolymer concrete prepared by the heat-activated slag and cement mixture geopolymer concrete preparation method proposed in Embodiments 1-3.

[0045] In actual production, the prefabricated floor slab is mass-produced in a factory by configuring a ratio of heat-activated slag and cement mixture geopolymer concrete. The factory realizes the reception of engineering slag, drying, screening and classification, high-temperature calcination to activate the activity of the mixture, and then excitation with an alkaline activator to form heat-activated slag and cement mixture geopolymer concrete. The factory adopts high-temperature curing to realize the entire production process of engineering prefabricated components, and finally prefabricates the prefabricated floor slab of this embodiment.

[0046] In this embodiment, the use of prefabricated floor slabs using geopolymer concrete mixed with heat-activated slag and cement as the main material in the building structure can be simulated and analyzed by finite element analysis software abaqus. Figure 3 to Figure 4 As shown, Figure 3 This is the mise analysis diagram of the precast slab concrete proposed in this embodiment. Figure 4 This is the reinforcement mise analysis diagram of the precast slab. It can be seen from the figure that the overall strength of the heat-activated slag and cement mixture geopolymer concrete precast slab is equivalent to that of C30 concrete, which can realize the application and promotion of heat-activated slag and cement mixture geopolymer concrete components.

[0047] The above are implementation methods provided in combination with specific contents, and it is not intended that the specific implementation of this application is limited to these descriptions. Any method structure similar to the present application, or a number of technical deductions or replacements based on the concept of the present application, should be considered as the protection scope of this application.

Claims

1. A method for preparing geopolymer concrete of a mixture of heat-activated slag and cement, characterized in that: The following steps are involved: a. Raw material preparation: obtain slag from the project excavation; b. Raw material pretreatment: drying and sieving the slag in step a to obtain dry slag powder and slag particles of suitable particle size; c. Activation: adding the slag powder and the slag particles in step b to mix with ordinary cement, and calcining them under high temperature conditions to obtain an activated mixture; d. Preparation of pure slurry: mixing the activated mixture in step c with an alkaline activator to prepare a pure slurry material; e. Concrete preparation: the clean slurry material in step d is mixed with coarse aggregate, fine aggregate and admixture to obtain heat-activated slag and cement mixture geopolymer concrete slurry, and a reinforcing agent is added to the heat-activated slag and cement mixture geopolymer concrete slurry.

2. The method for preparing geopolymer concrete of heat-activated slag and cement mixture according to claim 1, characterized in that: In step b, the drying temperature is 100-110° C., the drying time is 24 hours, and the particle size of the slag particles is less than or equal to 1.5 mm and 5-25 mm.

3. The method for preparing geopolymer concrete of heat-activated slag and cement mixture according to claim 1, characterized in that: In step c, the high temperature condition is 700-750° C., the calcination time is 2 hours, and the particle size of the slag particles is less than or equal to 1.5 mm.

4. The method for preparing geopolymer concrete of heat-activated slag and cement mixture according to claim 1, characterized in that: In step d, the alkaline activator is sodium hydroxide and water glass, and the addition amount thereof is controlled between 6% and 10% by weight of the total amount of the liquid activator and the solid raw materials.

5. The method for preparing geopolymer concrete of heat-activated slag and cement mixture according to claim 1, characterized in that: In the mixing process of step e, the water-to-solid ratio is 20% to 30%.

6. The method for preparing geopolymer concrete of heat-activated slag and cement mixture according to claim 1, characterized in that: The weight mix ratio of the slag polymer concrete in step e is activated mixture: water glass: sodium hydroxide: fine aggregate: coarse aggregate: water = 1: 0.3-0.4: 0.3-0.4: 2-3: 2-3: 0.1-0.2, the coarse aggregate is the slag particles with a particle size of 5-25 mm, and the fine aggregate is medium sand with a particle size of 1.0 mm-2.0 mm and a fineness modulus of 2.3-3.

0.

7. The method for preparing geopolymer concrete of heat-activated slag and cement mixture according to claim 1, characterized in that: The admixtures include S105 grade ground granulated blast furnace slag and F class fly ash. The particle size of the F class fly ash is less than 45 μm, its specific surface area is 400 m² / kg~450 m² / kg, and the admixture amount ranges from 5 to 8%; the particle size of the S105 grade ground granulated blast furnace slag is less than 45 μm, its specific surface area is 500 m² / kg~520 m² / kg, and the admixture amount ranges from 4 to 6%.

8. The method for preparing geopolymer concrete of heat-activated slag and cement mixture according to claim 1, characterized in that: The reinforcing agent is steel fiber, and the dosage range is 1.0% to 1.5%.

9. A prefabricated floor slab, comprising a floor slab body (1), wherein a plurality of groups of truss bars (2) are evenly arranged on the floor slab body (1), characterized in that: The material of the floor slab body (1) is the heat-activated slag and cement mixture geopolymer concrete prepared by the method for preparing the heat-activated slag and cement mixture geopolymer concrete according to any one of claims 1 to 8.